THE THE DIFFERENCES GIVING OF ENDORPHINE MASSAGE TOWARDS REDUCTION OF LABOR PAIN 1 ACTIVE PHASE IN PMB TIAS SUSIANAH, S.TR. KEB NORTH LAMPUNG IN 2020: THE DIFFERENCES GIVING OF ENDORPHINE MASSAGE TOWARDS REDUCTION OF LABOR PAIN 1 ACTIVE PHASE - Febrianti; Iis Tri Utami; Rini Wahyuni; Wiwi Febriani (Jurnal Maternitas Aisyah (JAMAN AISYAH), 2021)
Labor that lasts without pain or mild pain is only 15%, 35% of labor is accompanied by moderate pain, 30% of labor is accompanied by severe pain and 20% of labor is accompanied by very severe pain. The impact of unresolved pain is not only painful for the mother but also for the fetus. Endorphine massage is a mild touch method that is used to manage pain. The purpose of this study was to determine the differences giving of the Endorphine massage technique on the reduction of labor pain in the active phase I at PMB Tias Susianah, S.Tr. Keb Lampung Utara in 2020 This type of research is an experiment with a static group comparison design, the population is all mothers undergoing labor in PMB Tias Susianah, S.Tr. Keb. The sampling technique used in this study was quota sampling, with a total sample of 30 respondents. The analysis used is the T test (independent sample t-test). The results obtained an average pain scale in maternity women treated with endorphine massage 5,467 with a minimum pain scale of 4 and a maximum of 8. The average pain scale in pregnant women who were not treated with endorphine massage 6.8 with a minimum pain scale of 5 and maximum 9. There is an differences giving of endorphine massage on the reduction of labor pain in the active phase in PMB Tias Susianah, S.Tr. Keb Lampung Utara in 2020 (P-value = 0.003 (p-value <α (0.05)). The endorphine massage technique is a good alternative to reduce labor pain. Therefore, it is suggested to have a training for health workers.